Determination of Total Sulfur in Agricultural Samples by High-Resolution Continuum Source Flame Molecular Absorption Spectrometry - Virgilio, Alex [UNESP]; Raposo, Jorge L. [UNESP]; Cardoso, Arnaldo Alves [UNESP]; Nobrega, Joaquim A.; Gomes Neto, José Anchieta [UNESP] (Amer Chemical Soc, 2011)
The usefulness of molecular absorption was investigated for the determination of total sulfur (S) in agricultural samples by high-resolution continuum source flame molecular absorption spectrometry. The lines for CS at 257.595, 257.958, and 258.056 nm and for SH at 323.658, 324.064, and 327.990 nm were evaluated. Figures of merit, such as linear dynamic range, sensitivity, linear correlation, characteristic concentration, limit of detection, and precision, were established. For selected CS lines, wavelength-integrated absorbance equivalent to 3 pixels, analytical curves in the 100-2500 mg L-1 (257.595 nm), 250-2000 mg L-1 (257.958 nm), and 250-5000 mg L-1 (258.056 nm) ranges with a linear correlation coefficient better than 0.9980 were obtained. Results were in agreement at a 95% confidence level (paired t test) with those obtained by gravimetry. Recoveries of S in fungicide and fertilizer samples were within the 84-109% range, and the relative standard deviation (n = 12) was typically < 5%.
Keywords: Total sulfur; fungicide; fertilizer; flame molecular absorption spectrometry; high-resolution continuum source atomic absorption spectrometry